A Security Analysis Of Iot Encryption: Sidechannel Cube Attack On Simeck32/64 - Buja, Alya Geogiana; Abdul Latip, Shekh Faisal; Ahmad, Rabiah (Academy and Industry Research Collaboration Center (AIRCC), 2018)
Simeck, a lightweight block cipher has been proposed to be one of the encryption that can be employed in the Internet of Things (IoT) applications. Therefore, this paper presents the security of the Simeck32/64 block cipher against side-channel cube attack. We exhibit our attack against Simeck32/64 using the Hamming weight leakage assumption to extract linearly independent equations in key bits. We have been able to find 32 linearly independent equations in 32 key variables by only considering the second bit from the LSB of the Hamming weight leakage of the internal state on the fourth round of the cipher. This enables our attack to improve previous attacks on Simeck32/64 within side-channel attack model with better time and data complexity of 235 and 211.29 respectively.